Endophytic Bacillus altitudinis Strain Uses Different Novelty Molecular Pathways to Enhance Plant Growth - Zhang, Dening; Xu, Hongli; Gao, Jingyao; Portieles, Roxana; Du, Lihua; Gao, Xiangyou; Borroto Nordelo, Carlos; Borrás-Hidalgo, Orlando (Frontiers in Microbiology, 2021)
The identification and use of endophytic bacteria capable of triggering plant growth is an important aim in sustainable agriculture. In nature, plants live in alliance with multiple plant growth-promoting endophytic microorganisms. In the current study, we isolated and identified a new endophytic bacterium from a wild plant species Glyceria chinensis (Keng). The bacterium was designated as a Bacillus altitudinis strain using 16S rDNA sequencing. The endophytic B. altitudinis had a notable influence on plant growth. The results of our assays revealed that the endophytic B. altitudinis raised the growth of different plant species. Remarkably, we found transcriptional changes in plants treated with the bacterium. Genes such as maturase K, tetratricopeptide repeat-like superfamily protein, LOB domain-containing protein, and BTB/POZ/TAZ domain-containing protein were highly expressed. In addition, we identified for the first time an induction in the endophytic bacterium of the major facilitator superfamily transporter and DNA gyrase subunit B genes during interaction with the plant. These new findings show that endophytic B. altitudinis could be used as a favourable candidate source to enhance plant growth in sustainable agriculture.